A script to highlight hydrophobicity and charge on protein surfaces - Hagemans, Dominique; van Belzen, Ianthe A. E. M.; Morán Luengo, Tania; Rüdiger, Stefan G. D. (Frontiers in Molecular Biosciences, 2015)
The composition of protein surfaces determines both affinity and specificity of protein-protein interactions. Matching of hydrophobic contacts and charged groups on both sites of the interface are crucial to ensure specificity. Here, we propose a highlighting scheme, YRB, which highlights both hydrophobicity and charges in protein structures. YRB highlighting visualises hydrophobicity by highlighting all carbon atoms that are not bound to nitrogen and oxygen atoms. The charged oxygens of glutamate and aspartate are highlighted red and the charged nitrogens of arginine and lysine are highlighted blue. For a set of representative examples, we demonstrate that YRB highlighting intuitively visualises segments on protein surfaces that contribute to specificity in protein-protein interfaces, including Hsp90/co-chaperone complexes, SNARE complex and a transmembrane domain. We provide YRB highlighting in form of a script that runs using the software PyMOL.